Canadian Digestive Health Foundation Public Impact Series: Gastroesophageal Reflux Disease in Canada: Incidence, Prevalence, and Direct and Indirect Economic Impact. (2010) - Fedorak, Richard N; van Zanten, Sander Veldhuyzen; Bridges, Ron
Abstract : The Canadian Digestive Health Foundation initiated a scientific program to assess the incidence, prevalence, mortality and economic impact of digestive disorders across Canada. The current article presents the updated findings from the study concerning gastroesophageal reflux disease – a condition that develops when the reflux of stomach contents causes troublesome symptoms and/or complications (Montreal definition).